2020
DOI: 10.1007/s13205-019-2015-y
|View full text |Cite
|
Sign up to set email alerts
|

Novel miRNA identification and comparative profiling of miRNA regulations revealed important pathways in Jinding duck ovaries by small RNA sequencing

Abstract: Functional studies have revealed miRNAs play pivotal roles in ovulation and ovary development in mammalians, whereas little is known about the miRNA function in ducks. In this study, miRNA deep sequencing in the ovary tissues was carried out to obtain the miRNA profile from ovaries before oviposition (BO) and after oviposition (AO) in Jinding duck. Overall, an average of 23,128,075 and 26,020,523 reads were identified in the BO and AO samples, respectively, and 6739 miRNAs were identified from them through fur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 52 publications
0
3
0
Order By: Relevance
“…Meanwhile, it was known that miRNAs were expressed in specific times and tissues, and these characteristics make miRNA detection more difficult. However, the deep sequencing technology performed in different species, different tissue, or different physiological conditions made it possible to detect the novel miRNAs, and accumulating novel miRNAs were identified in the ovary of other species, such as human ( Xu et al, 2016 ), bovine ( Navakanitworakul et al, 2016 ), zebrafish ( Zayed et al, 2019 ), sheep ( Miao et al, 2016 ), duck ( Yang et al, 2020 ) and chicken ( Wu et al, 2017 ). For porcine miRNA detection, previous studies have identified several novel miRNAs in lung, hepatic, testes, muscles, and adipose ( Wang et al, 2017a ; Zhang et al, 2018b ; Ford et al, 2018 ; Luo et al, 2018 ; Liu et al, 2019a ).…”
Section: Discussionmentioning
confidence: 99%
“…Meanwhile, it was known that miRNAs were expressed in specific times and tissues, and these characteristics make miRNA detection more difficult. However, the deep sequencing technology performed in different species, different tissue, or different physiological conditions made it possible to detect the novel miRNAs, and accumulating novel miRNAs were identified in the ovary of other species, such as human ( Xu et al, 2016 ), bovine ( Navakanitworakul et al, 2016 ), zebrafish ( Zayed et al, 2019 ), sheep ( Miao et al, 2016 ), duck ( Yang et al, 2020 ) and chicken ( Wu et al, 2017 ). For porcine miRNA detection, previous studies have identified several novel miRNAs in lung, hepatic, testes, muscles, and adipose ( Wang et al, 2017a ; Zhang et al, 2018b ; Ford et al, 2018 ; Luo et al, 2018 ; Liu et al, 2019a ).…”
Section: Discussionmentioning
confidence: 99%
“…For instance, Guo et al (2021) found that miR-301a-5p regulates chicken spermatogenesis through the transformation growth factor-beta 2 ( TGFβ2 ). Similarly, Yang et al (2020) suggest that miRNAs may have a potential role in the development and reproduction of duck ovaries. Circular RNAs ( circRNAs ) are noncoding RNAs with stable and covalently closed loops ( Memczak et al, 2013 ).…”
Section: Introductionmentioning
confidence: 99%
“…The Youxian sheldrake duck (YX, Hunan Province), a versatile breed popular for its high egg-production rate and excellent egg quality [ 7 , 8 ]. The Jinding duck (JD, Fujian Province) is popular for its high laying performance [ 9 , 10 ]. A study on artificial selection between JD and meat-type ducks found that the candidate genes of JD ducks are mainly enriched in embryonic development function and metabolic pathways [ 11 ].…”
Section: Introductionmentioning
confidence: 99%